2021
DOI: 10.3389/fonc.2021.677826
|View full text |Cite
|
Sign up to set email alerts
|

RBM10 Deficiency Is Associated With Increased Immune Activity in Lung Adenocarcinoma

Abstract: IntroductionRBM10 is one of the frequently mutated genes in lung adenocarcinoma (LUAD). Previous studies have confirmed that RBM10 could suppress the disease progression and cell proliferation in LUAD, but its loss-of-function mutations are more frequent in early-stage disease and decrease with the advancement of the clinical stage. This is contradictory to its role of tumor suppressor. Here, we conducted a systematic analysis to elucidate whether there was other potential biological significance of RBM10 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Intriguingly, a previous report showed that RBM10 deficiency in LUAD is associated with enriched immune pathways, elevated tumor mutational burden, and increased human leukocyte antigens (HLA) expression, suggesting that RBM10 deficiency may enhance anti-tumor immunity in LUAD 88 . In agreement with this, our RBM10 transcriptome in HCC827 and H1299 cell lines showed that RBM10 depletion leads to increased expression of proinflammatory cytokines such as IL1R2, TNFRSF1B, BMP2, IL7R and CCL2.…”
Section: Discussionmentioning
confidence: 98%
“…Intriguingly, a previous report showed that RBM10 deficiency in LUAD is associated with enriched immune pathways, elevated tumor mutational burden, and increased human leukocyte antigens (HLA) expression, suggesting that RBM10 deficiency may enhance anti-tumor immunity in LUAD 88 . In agreement with this, our RBM10 transcriptome in HCC827 and H1299 cell lines showed that RBM10 depletion leads to increased expression of proinflammatory cytokines such as IL1R2, TNFRSF1B, BMP2, IL7R and CCL2.…”
Section: Discussionmentioning
confidence: 98%
“…RBM10 is an RNA binding protein known to be a TFEB fusion partner in MIT translocation‐associated RCC [ 26 ]. Somatic mutations in RBM10 have also been detected in NSCLC tumours and were found to be associated with increased influx of CD8+ T cells and IFN‐G transcriptional signatures [ 27 ]. Therefore, RBM10 and FBXW7 mutations may act as a biomarker in patients with ccRCC receiving immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatics study found that in HCC, the RBM10 expression was positively correlated with infiltration of CD8 + T cell, as well as the expression of PD-1 and PD-L1 [8]. However, a recent report showed that CD8+ T cells showed a higher level of infiltration in LUAD with RBM10 deletion [16]. In this study, we found that the RBM10 expression was negatively correlated with B cells, CD8+ T cells, neutrophils, macrophages, and DC cell infiltration levels in most tumor types, indicating that RBM10 was likely to affect tumor development and prognosis by impacting the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Pang et al [8] have shown that the high RBM10 expression is positively linked with most immune cell infiltrates and the expressions of PD-1 and PD-L1 in hepatocellular carcinoma (HCC). In addition, a recent research confirms that the low RBM10 expression significantly increases the immune activity of LUAD and is negatively linked with CD8+ T cells having a tumorsuppressive effect, which makes it evident that RBM10 is linked with immune infiltration [16]. Most current studies about the role of RBM10 in cancer have been focused on an individual or limited to some specific tumor types.…”
Section: Introductionmentioning
confidence: 92%